Kontribusi Manajemen Peserta Didik terhadap Pendidikan Seksual - Minggusta Juliadarma (Sekolah Tinggi Ilmu Tarbiyah Al-Urwatul Wutsqo Jombang, 2021)
So far, education experts have contributed a lot of thoughts on tips on child sexual education, but the operation of the education process is only through informal education, which is only in the family environment. This study seeks to present the flow of the sexual education process of children at the school level as an integral part of the learning process. This study discusses the contribution of student management to sexual education of children in schools. This study uses library research methods and uses documentation study as a data collection technique. The results revealed that the process of implementing sexual education in students can be carried out in three stages of activities, namely the stages of admitting new students, the learning process, guidance and monitoring. The first stage is through managing new student orientation activities which are divided into male and female groups, new students are accustomed not to mingle with the opposite sex. This activity should also be used by the school to socialize school rules that contain sexual education values. The second stage, management of the learning process in the form of managing student groupings based on gender (gender grouping); determining the learning method through the expository method, discussion method, exemplary method, and habituation method; as well as managing learning programs by incorporating sexual education values ??into formal subjects such as Biology, Sociology, Morals, and Fiqh. The next stage is to carry out structured guidance related to sexual education coaching under the supervision of guidance and counseling teachers. The final stage in the series of sexual education processes in schools is monitoring activities that involve all stakeholders in the school environment such as the principal, vice principal in student affairs, homeroom teachers, subject teachers, guidance and counseling teachers and even parents.